MAPKs in the early steps of senescence implemEMTation - Anerillas, Carlos; Altés, Gisela; Gorospe, Myriam (Frontiers in Cell and Developmental Biology, 2023)
Evidence is accumulating that the earliest stages of the DNA damage response can direct cells toward senescence instead of other cell fates. In particular, tightly regulated signaling through Mitogen-Activated Protein Kinases (MAPKs) in early senescence can lead to a sustained pro-survival program and suppress a pro-apoptotic program. Importantly, an epithelial-to-mesenchymal Transition (EMT)-like program appears essential for preventing apoptosis and favoring senescence following DNA damage. In this review, we discuss how MAPKs might influence EMT features to promote a senescent phenotype that increases cell survival at the detriment of tissue function.